Upaya Meningkatkan Gairah Keagamaan Melalui Pendampingan Kegiatan Perayaan Tahun Baru Islam - Rizky Khofifah; Yuspita Ayu; Muhammad Sahman Rangkuti; Iklil Ahmad Awlia Lubis; Hasanuddin Hasanuddin; Yusnani Yusnani; Nur Aida Nasution; Sonia Lestari Harahap; Syarifah Aini (Jurnal Kabar Masyarakat, 2024)
Real Work Lectures (KKN) are a learning process for undergraduate students Mandailing Natal State Islamic College. Developing through community service activities in various areas of community life. The implementation of this community service program aims to develop empathy and concern for various real problems faced by society and the development of society. Sustainable development is needed to smarten the lives of the nation's people and achieve people's welfare. (Janosik, 2005). As technology develops, it must be accompanied by the development of human resources in the fields of education and economics.Islam is a religion brought by the Prophet Muhammad SAW to Arabia in the 7th century in the Arab region. Islam is based on the belief in the oneness of ALLAH, (tauhid) and considers the Al Qu'an to be a holy book that was revealed directly from ALLAH SWT to the Prophet Muhammad SAW. The Muslim ummah, followers of the Islamic religion, spread worship such as prayer or worship, fasting during the month of Ramadan, zakat, hajj, and jihad. The Islamic religion teaches values such as justice, compassion, simplicity and brotherhood. Muslims are expected to live according to religious teachings and follow the moral principles set out in Islam. Islam also has a significant influence on culture, art, architecture, literature and legal systems in various countries where the majority are Muslim. It is important to remember that Islam has various traditions and sects such as Sunni, Shiite, Sufi and others, which provide variations in practices and interpretations of the religion. The Islamic religion also has a rich and complex history, and has followers all over the world.